Green Constitutional Paradigm for Sustainable Environmental Development in the Capital of Archipelago: A Comparative Research with France and Ecuadorian Constitution - Kusworo, Daffa Ladro; Arsil, Fitra (Unifikasi : Jurnal Ilmu Hukum, 2024)
Green constitution is the solution to various kinds of public concerns related to the decline of environmental functions. Although the 1945 Constitution, attempted to contain articles on the environment, Indonesia was still classified as a country that only regulated it formally. The implication was the inadequate exploration of the National Capital City developed based on the concept of smart forest city. This led to environmental damages in the form of deforestation and lengthy sustainable recovery. Normative methods were adopted to examine the environmental aspects as a state of law. This was further analysed in view of the relevant issues. The 1945 Constitution's accommodation of green constitution was still far behind compared to France and Ecuador, which both constitutionalised environmental law norms. The French constitution, for example, mandated that every draft law produced by its Parliament must follow the provisions and standards stipulated in the Environmental Charter. Additionally, development of National Capital City towards the conditions and threats of environmental sustainability, strengthened the conceptual foundations of related issues.